Design Challenges for an Autonomous Unmanned Aerial Vehicle With Hybrid Lift and Propulsion - Alysson Nascimento de Lucena; Neusa Maria Franco de Oliveira; Bruno Marques Ferreira da Silva; Raimundo Carlos Silverio Freire Junior; Luiz Marcos Garcia Goncalves (IEEE Access)
Minimization of energy consumption with the longest flight time and distance is one of the main challenges in the development of unmanned aerial vehicles (UAV). Vertical take-off and landing (VTOL) is another feature that makes handling such platforms easier. Considering these requirements, we propose the architectural design of a double-hybrid UAV, conceptualized and built as a flying wing with tractor configuration with a combustion engine propeller and an electric multirotor with 3 propeller sets. We performed several tests to validate the proposed UAV model, including take-off, horizontal flight, transition tests, and also tests on autonomy (flight time and distance). As a verification of the tool usefulness, the architectural sketch of our proposal has been granted a patent from the Intellectual Property Institute (Brazil) under the number BR-10-2015-032525-8. The main contribution is the architectural design and conceptualization of the double-hybrid UAV, which consists of easy-to-follow procedural steps that can be reproduced in a simple fashion anywhere.